Tariff politics and congressional elections: exploring the Cannon Thesis. (July 2017) - Clarke, Andrew J; Jenkins, Jeffery A; Lowande, Kenneth S
While a number of studies have examined the politics of tariff decision-making in the United States, little work has examined the subsequent political effects of tariff policy. We help fill this gap in the literature by analyzing—both theoretically and empirically—the electoral implications of tariff revision. Specifically, we investigate the veracity of the Cannon Thesis—the proposition advanced by Speaker Joe Cannon in 1910 that the majority party in the U.S. House was punished when it made major revisions to the tariff. We find that from 1877 to 1934 major tariff revisions were, on average, associated with a significant loss of votes for majority-party members—both regionally and nationally—that translated into a loss of House seats. We find support for the notion that major tariff revisions generated inordinate uncertainty among various business interests, which the opposition party could then use (by leveraging fear and market instability) to mobilize its base and gain ground in the following election. Our results provide a new explanation for the delegation of tariff policymaking to the executive branch.